On the Development of New Revolution Typology - Vitaly Aleksandrovich Volkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Revolution phenomena is changes through history of humanity. Understanding of different modern political processes become possible with revolution theory. At the beginning of the XXI c. in the world, a wave of «color revolutions» and then the «Arab Spring» took place. Our main task we see as the creation of a working revolution classification. We would use worldsystem theory and theory of cultural hegemony.